Volume 1: Offshore Technology; Special Symposium on Ocean Measurements and Their Influence on Design 2007
DOI: 10.1115/omae2007-29325
|View full text |Cite
|
Sign up to set email alerts
|

Development and Qualification of Alternative Solutions for Improved Fatigue Performance of Deepwater Steel Catenary Risers

Abstract: Several initiatives have been undertaken by the operators, engineering companies, product manufacturers, and regulatory bodies to enable increased use of steel catenary riser (SCR) design in development of deepwater and ultra-deepwater fields. Some of these efforts focus on improvement in understanding of soil-structure interaction at SCR touch down zone (TDZ) and its impact on fatigue damage estimates through analytical studies, laboratory testing, or in-field monitoring of SCR behavior. Through recent studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…e shear strength is the opposite, decreasing first and then decreasing again [15][16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 97%
“…e shear strength is the opposite, decreasing first and then decreasing again [15][16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 97%
“…However, for non-symmetrical relocation programs, the patterns will be skewed about the nominal station. In previous work for symmetric relocation optimisation for single SCR [31], it was found that the optimum relocation program (𝛼, 𝑅, 𝑝) was (30deg, 5%, 19). A further investigation of this relocation program showed that although 19 stations gave the least effective fatigue damage, the number of stations beyond 𝑝 = 9 along 𝛼 = 30deg, for 𝑅 =5% contributed very little reduction to the effective damage of the SCR TDZ as shown in Table 4 and Figure 8.…”
Section: Analysis Datamentioning
confidence: 99%
“…The application of alternative materials for SCR pipes can provide increased strength and resistance to corrosion. An example of such material is titanium [2,[17][18][19][20], which can significantly improve the SCR ability to accommodate considerable stress and fatigue damage considering its high flexural rigidity. Many advancements have been made in riser soil interaction modelling, such as developing non-linear riser soil interaction models [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, at the touchdown zone, a longer section of the SCR interacts in a complex way with the nonlinear seabed, resulting in high and intricate fatigue response patterns that pose great challenges to manage. Several efforts have been committed by research institutions and the offshore industries to increase the application of SCRs for deepwater hydrocarbon extraction [11][12][13]. These solutions include the SCR configuration change such as steel lazy wave and shaped riser solutions [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32], the alternative material application for SCR design such as high strength material including titanium for the riser pipe joint [2,11,[33][34][35], the advancement in riser soil interaction modelling such as the development of non-linear riser soil interaction models [36][37][38], the decoupling of SCR from vessel motion such as the uncoupled steel catenary riser systems [39][40][41][42], the vessel relocation to effect fatigue damage spreading along the SCR TDZ [12,[43][44][45], the use of upset pipe end and titanium welding connection to improve the life of the riser at welded joints [11,35...…”
Section: Introductionmentioning
confidence: 99%